Luminescent silica- based nanomaterials for biomedicine - Campelo, Adrián Esteban (2019)
Silicon dioxide (SiO2), a material known as “silica” presents properties that make it a good candidate as a biomaterial: it has a very labile surface for functionalization, it is easy to synthesize and it is biocompatible. Calcination after synthesis of silica NPs yields luminescent nanomaterials. Fluorescent NPs themselves would offer enhanced functionality in terms of these properties with respect to conventional organic fluorophores. In this work, the influence of the synthesis method on the hydrodynamic diameter of silica fluorescent NPs was studied in order to obtain an optimal formulation as potential theranostic. Stöber process, involving tetraethylorthosilicate (TEOS) and 3-aminopropyltriethoxysilane (APTES), has been applied to obtain different formulations from increasing APTES initial concentration. After synthesis, the NPs were calcined at 450 °C. Characterization was performed by FTIR, TEM, DRX, fluorescence spectroscopy/microscopy and DLS to determine hydrodynamic diameter (Hd). NPs synthesized without APTES do not present fluorescent properties, while the APTES containing NPs are fluorescent. Increasing concentration of APTES induces larger NPs with low stability in physiological medium. The optimal synthesis condition resulted with a TEOS:APTES ratio of 1:0.1 rendering a Hd of 450 nm with polydispersion index near 0.20. This formulation is suitable for biomedical applications in terms of Hd and stability as potential theranostic agent for multiple pathologies, including Chronic Lymphocytic Leukemia that is of our particular interest. CLL is the most common adult leukemia in Western countries and is defined by the accumulation of mature, CD5+ B lymphocytes in peripheral blood, bone marrow and secondary lymphoid organs. Despite important progress in treatment, relapse occurs and this leukemia remains incurable in many cases. New therapeutic approaches by innovative tools acting in synergism with the last therapies approved in CLL are desirable.